2019
DOI: 10.3389/fnbeh.2019.00151
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stress on Gamma Oscillations in the Rat Nucleus Accumbens During Spontaneous Social Interaction

Abstract: Alteration in social behavior is one of the most debilitating symptoms of major depression, a stress related mental illness. Social behavior is modulated by the reward system, and gamma oscillations in the nucleus accumbens (NAc) seem to be associated with reward processing. In this scenario, the role of gamma oscillations in depression remains unknown. We hypothesized that gamma oscillations in the rat NAc are sensitive to the effects of social distress. One group of male Sprague-Dawley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Gamma oscillations have also been monitored during social interactions in the nucleus accumbens of rats that were exposed to chronic social defeat. This study observed a significant reduction of power increase in high gamma activity (61–90 Hz) for stress‐exposed rats as compared to the non‐stressed group (Iturra‐Mena et al., 2019).…”
Section: E/i Balance May Influence Neuronal Population Dynamics Including Gamma Power Which Are Important To Mood and Memorymentioning
confidence: 64%
“…Gamma oscillations have also been monitored during social interactions in the nucleus accumbens of rats that were exposed to chronic social defeat. This study observed a significant reduction of power increase in high gamma activity (61–90 Hz) for stress‐exposed rats as compared to the non‐stressed group (Iturra‐Mena et al., 2019).…”
Section: E/i Balance May Influence Neuronal Population Dynamics Including Gamma Power Which Are Important To Mood and Memorymentioning
confidence: 64%
“…Conveniently, most of the CAD files designed by developers for multichannel recordings are now available from cloud-based repositories, such as Mendeley data, and laboratory websites, which enables researchers to freely create these devices. Furthermore, wireless recording systems are recently available ( Zuo et al, 2012 ; Martinez et al, 2018 ; Iturra-Mena et al, 2019 ), which are especially useful for stress research because they reduce the physical stress of animals.…”
Section: Methods For Oscillotherapeutic Studies Using Rodentsmentioning
confidence: 99%
“…This would increase the inhibitory activity of the PV-FSI on the medium spiny neurons (MSN), which would generate oscillations in -frequency range. Conversely, stress-induced rats by social interaction with unfamiliar conspecific exhibited decreased oscillations in the NAc, as a consequence of a decreasing in the levels of DA in the NAc which provoked a decrease in the activity of the PV-FSI 54 , 55 . This might also suggest that PVKO mice are likely to be characterized by a reduced sensitivity to reward state, but our baseline condition could not reveal it because mice were left alone during LFP recordings.…”
Section: Discussionmentioning
confidence: 91%